Clopidogrel-induced drug-induced hypersensitivity syndrome following percutaneous coronary intervention: a case report of therapeutic dilemma and management strategy - Wang, Sikun; Zhou, Jiang; Sun, Yuanhua (Frontiers in Pharmacology, 2026)
BackgroundDrug-induced hypersensitivity syndrome (DIHS), also known as drug reaction with eosinophilia and systemic symptoms (DRESS), is a rare but potentially life-threatening adverse drug reaction. Clopidogrel induced DHS following percutaneous coronary intervention (PCI) presents a unique therapeutic challenge due to the critical need for dual antiplatelet therapy to prevent stent thrombosis.Case summaryA 70-year-old male underwent emergency PCI with multiple stent implantation for unstable angina with three-vessel coronary disease. Standard dual antiplatelet therapy (aspirin 100 mg daily and clopidogrel 75 mg daily) was initiated post-procedure. One hour after PCI, the patient developed anaphylactic shock initially attributed to contrast agent allergy. Two weeks post-discharge, he presented with recurrent skin rash, hypotension, gastrointestinal bleeding, fever, and eosinophilia, consistent with DIHS. Multidisciplinary consultation confirmed clopidogrel-induced DIHS using established diagnostic criteria. Despite the high risk of stent thrombosis, dual antiplatelet therapy was discontinued due to life-threatening complications. The patient was successfully managed with indobufen and low dose corticosteroids, resulting in complete symptom resolution.ConclusionThis case highlights the diagnostic complexity of clopidogrel-induced DIHS and presents the detailed account of successful management of it. Early recognition using standardized diagnostic criteria and multidisciplinary management are crucial for patient outcomes.